Prokaryotic Arsenate Reductase Enhances Arsenate Resistance in Mammalian Cells - Wu, Dan; Tao, Xuanyu; Wu, Gaofeng; Li, Xiangkai; Liu, Pu (Recent Patents on Food, Nutrition & Agriculture, 2014)
Arsenic is a well-known heavy metal toxicant in the environment. Bioremediation of heavy metals has been proposed as a low-cost and eco-friendly method. This article described some of recent patents on transgenic plants with enhanced heavy metal resistance. Further, to test whether genetic modification of mammalian cells could render higher arsenic resistance, a prokaryotic arsenic reductase gene arsC was transfected into human liver cancer cell HepG2. In the stably transfected cells, the expression level of arsC gene was determined by quantitative real-time PCR. Results showed that arsC was expressed in HepG2 cells and the expression was upregulated by 3 folds upon arsenate induction. To further test whether arsC has function in HepG2 cells, the viability of HepG2-pCI-ArsC cells exposed to arsenite or arsenate was compared to that of HepG2-pCI cells without arsC gene. The results indicated that arsC increased the viability of HepG2 cells by 25% in arsenate, but not in arsenite. And the test of reducing ability of stably transfected cells revealed that the concentration of accumulated trivalent arsenic increased by 25% in HepG2-pCI-ArsC cells. To determine the intracellular localization of ArsC, a fusion vector with fluorescent marker pEGFP-N1-ArsC was constructed and transfected into.HepG2. Laser confocal microscopy showed that EGFP-ArsC fusion protein was distributed throughout the cells. Taken together, these results demonstrated that prokaryotic arsenic resistant gene arsC integrated successfully into HepG2 genome and enhanced arsenate resistance of HepG2, which brought new insights of arsenic detoxification in mammalian cells.
Keywords: HepG2